Análise das alterações agudas eletroquímicas e do distúrbio ácido-básico em competidoras de ultramaratona de montanha durante uma prova de 45 km - Fernandes, Priscila (2019)
Few studies have investigated the acute electrochemical alterations and the acid-base disturbance in mountain ultramarathons, female. The present study aimed to analyze acute electrochemical changes and acid-base disturbance in mountain ultramarathon competitors after a 45-km race. The parameters of 19 women with a mean age of 42 ± 5.8 years and total body mass of 56.78 ± 7.42 kg were analyzed. The blood samples were analyzed using the GEM Premier 3000 Blood Gas Analyzers, and the following parameters were evaluated: pH, pO2, pCO2, HCO₃⁻, Na +, K +, Ca2 +, Lac- and Hct. To compare the electrochemical changes and the acid-base disorder Pre and Post-test, the t-test was performed paired, adopting as significance level p0,05. The electrochemical analysis showed values for K + Pre-test of 4.99 ± 0.64 mmol and Post-test of 3.87 ± 0.73 mmol / L (p˂0,0001). The Hct Pre-test of 44.74 ± 0.06% and Post-test of 42.63 ± 3.05% (p = 0.004). Lac-Pretest was 2.52 ± 0.74 mmol / L and Post-test 3.63 ± 2.62 mmol / L (p = 0.01). On the gas analysis, the results of the Pre-test for HCO3- 25.54 ± 2.55 mmol / L and for the Post-Test 21.08 ± 3.09 mmol / L, the pCO2 Pre-test 38, 47 ± 4.63 mm / Hg and Post-Test of 33.58 ± 4.96 mm / Hg (p˂0,0001) and the pO2 Pre-test 63.68 ± 8.24 mm / Hg and Post-Test 58.68 ± 6.67 mm / Hg (p = 0.03). Electrochemical analysis and acid-base disturbance showed non-statically significant acid-base disturbance, hypocapnia, and respiratory alkalosis.